Case report of breast implant-associated anaplastic large cell lymphoma and a call for increased awareness - Long, Brittany; Dissanayake, Thushara (International Surgery Journal, 2022)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare but serious complication of breast implants. The incidence of BIA-ALCL varies between 1:9121 and 1:13745, and a recent meta-analysis found that countries where specific monitoring measures have been implemented have higher rates of cases. While a significant complication, there is no current evidence to support surgical risk management strategies to prevent BIA-ALCL. Many countries have adopted a model of surveillance, and in Australia the Therapeutic Goods Administration has endorsed data collection through the Australian Breast Device Registry (ABDR). We present a case of a 67-year-old woman who presented to her GP with 2 months of left breast swelling, on a background of a left breast implant in 2004. MRI of the left breast demonstrated a large peri-implant fluid collection, and cytology confirmed BIA-ALCL, CD30-positive and ALK-negative. She underwent a capsulectomy and final histology demonstrated a Breast Implant-Associated Anaplastic Large Cell Lymphoma with focal penetration of neoplastic cells beyond the capsule and into pericapsular fat (stage T4). While development of registries and national guidelines has ensured the safeguarding of health outcomes for patients moving forward, there is still a concern for women with pre-existing breast implants who are unaware of the risk of BIA-ALCL. This case highlights the importance of raising awareness and providing support to primary health care providers to ensure their patients are given the necessary information to avoid this rare, but serious complication.